The skin game - Hitchcock, Alfred, 1899-1980; Gwenn, Edmund, 1875-1959; Haye, Helen, 1874-1957; Esmond, Jill, 1908-1990 (Canal, 1931)
Η μάχη δύο οικογενειών για ένα κομμάτι γης σε ένα μικρό αγγλικό χωριό.